How do software architects perceive technical debt in Colombian industry? An analysis of technical debt causes (2020)
Technical debt is a metaphor used to describe technical decisions that can give the company a benefit in the short term but possibly hurting the overall quality of the software in the long term. Architectural decisions are considered one of the most common sources of technical debt, therefore, it becomes relevant to understand what causes lead to technical debt from the point of view of software architects. To accomplish this task, we used a survey research method to collect and analyze a corpus of 28 software architects from Colombia, as a part of the InsighTD project. Results showed that inappropriate planning is the most cited technical debt cause by software architects. However, results differ when comparison against engineers and manager are performed. Innacurate time estimate and producing more without quality were the most selected causes of technical debt according to engineers and managers. To improve this comparison, the rank-biased overlapping technique was used. As more elements were compared, more similar were these lists of causes among all three roles.